PENGARUH PEMBERIAN PAKAN ITIK DENGAN LIMBAH UDANG DAN LIMBAH KULIT KACANG KEDELAI YANG DIBERI PROBIOTIK TERHADAP PRODUKSI DAN WARNA KUNING TELUR - Sindu Akhadiarto (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
The objective of this study was to utilize the superiority of agricultural waste in form of soybean hull and shrimp wastes and their combination on egg layer duck. This feed contains starbio probiotic functions for fiber digestion (soybean hull waste) and chitin (from shrimp waste). The expectation was that there would be duck ration which is able to increase egg production and quality and brighter reddish egg-yolk which is attractive and full of nutritions. The research was conducted in three stages. Stage I is Nutrient Digestional Value Test on the formula of soybean hull and shrimp wastes mixture on Duck Feed Contained Starbio.